Moral Education in the Story of Prophet Yusuf: A Thematic Study of Classical and Contemporary Tafsir - Lischontina, Maylina; Septiawadi, Septiawadi; Badi'ah, Siti (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2025)
Moral education is a crucial aspect of human character formation. The moral crisis of the modern era demands a strengthening of education grounded in divine values. The Qur’an presents the story of Prophet Yusuf as a moral exemplar encompassing honesty, patience, self-control, and leadership. This study aims to examine the moral educational values in the story of Prophet Yusuf based on classical and contemporary exegesis. The research employs library research with a thematic (tafsir maudhu’i) approach. The findings show that classical exegesis (such as Ibn Kathir and al-Ṭabari) emphasizes moral aspects through a narrative-based approach, while contemporary exegesis (such as Quraish Shihab and al-Maraghi) highlights the moral relevance for modern life. The study concludes that the moral education embedded in the story of Prophet Yusuf remains relevant and can serve as a foundation for Islamic education in the present era.